Daya Hambat Ekstrak Kulit Buah Apel (Malus sylvestris Mill.) Varietas Manalagi Terhadap Pertumbuhan Streptococcus viridians - Febriana Tria N; Tantin Ermawati; Dwi Warna Aju Fatmawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2014)
Most of root canal infections are caused by Streptococcus viridans. Apple peel variety of manalagiextract is alleged to control the number of Streptococcus viridans's population. This extract contains antibacterialcompound such us polyphenols derivative (catechin, chlorogenic acid, quercetin). The purpose of this study was tofind out antibacterial activity of apple peel extract variety of manalagi against the growth of Streptocossus viridans.The method of this study was well diffusion method with 6 treatment groups (n=12). Each petridish was filled BHI-Aand inoculated by Streptococcus viridans followed by making 6 wells using sterile straws (diameter 5 mm). Extracts100%, 75%, 50%, 25%, positive control, and negative control were added into the wells at concentration of 5 μL foreach material. After that, the incubation was carried out at a temperature of 37oCfor 24 hours then inhibitory zoneswere measured. The results of this study showed that there were inhibitory zones in all treatment groups, exceptnegative control. The conclusion is that apple peel variety of manalagi extract has antibacterial activity against thegrowth of Streptococcus viridans with minimum inhibitory concentration of 25%.